2010
DOI: 10.1364/oe.18.013772
|View full text |Cite
|
Sign up to set email alerts
|

Known plaintext attack on double random phase encoding using fingerprint as key and a method for avoiding the attack

Abstract: We have shown that the application of double random phase encoding (DRPE) to biometrics enables the use of biometrics as cipher keys for binary data encryption. However, DRPE is reported to be vulnerable to known-plaintext attacks (KPAs) using a phase recovery algorithm. In this study, we investigated the vulnerability of DRPE using fingerprints as cipher keys to the KPAs. By means of computational experiments, we estimated the encryption key and restored the fingerprint image using the estimated key. Further,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 11 publications
1
41
0
1
Order By: Relevance
“…Despite the fact that a plurality of attacks have been designed to break DRPE systems [23][24][25][26][27][28][29][30], different approaches were suggested to improved security in DRPE. For instance, it has been demonstrated that quantum encryption systems that works with few photons are very secure [31,32].…”
Section: Encryption and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that a plurality of attacks have been designed to break DRPE systems [23][24][25][26][27][28][29][30], different approaches were suggested to improved security in DRPE. For instance, it has been demonstrated that quantum encryption systems that works with few photons are very secure [31,32].…”
Section: Encryption and Validationmentioning
confidence: 99%
“…Consequently, additional improvements with optical security techniques [16][17][18][19][20][21][22] could be adapted to be used with focused beams. To avoid conventional attacks against the information encrypted in the longitudinal component [23][24][25][26][27][28][29][30], the use of quantum imaging techniques is suggested [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…This area of research includes image encryption [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], authentication [16][17][18][19][20][21][22][23][24], and compression or secure storage [25,26]. Authenticating sensitive information is critical to discovering tampering caused by a miscreant.…”
Section: Introductionmentioning
confidence: 99%
“…The most common encryption schemes were double random phase encoding combining other encryption method, which could improve security of the cryptosystem. Because of double random phase encoding system was linear, some researchers proposed various attack schemes [11][12][13][14][15][16]. In recent years, authentication and verification based on DRPE and photon counting imaging techniques [6][7][8][9] and ghost imaging [17][18][19][20][21][22] have attracted the interest of the research community.…”
Section: Introductionmentioning
confidence: 99%